KEANEKARAGAMAN JENIS TUMBUHAN BERKHASIAT OBAT DI HUTAN KAMPUS UNIVERSITAS TANJUNGPURA PONTIANAK - Megawati, Megawati; Ekyastuti, Wiwik; Herawatiningsih, Ratna (Universitas Tanjungpura, 2020)
Since a long time ago, Indonesians have already known and utilized medicinal plants to overcome health problems. Tanjungpura University (UNTAN) was a part of the green open space in Pontianak, where there are green vegetation surroundings, whether plants , stakes, poles, or trees. Some of those plants have the potential to come as a medicinal. This research aimed to find the value of medicinal plantsâ€™ diversity in Tanjungpura University forestry. The advantage of this research will hopefully provide some knowledge about medicinal plant which later can be managed and preserved in Tanjungpura University. This research was conducted in the secondary forest of forestry faculty and Tanjungpura University Arboretum. This research used survey listen double ply technique as the method. Every surveillance partition have a size of 20 x 20 m, consisting of 8 partition on each forest, made up a totalÂ of 0,64 Ha. Based on the research findings of medicinal plants in secondary Arboretum forest at seedling levels = 1,03, sapling = 0,88, pole = 0,19, tree = 0,97 while the secondary forest of forestry faculty at the seedling level = 0,79, sapling = 0,58, pole = 0,55, tree = 0,86.Keyword : Arboretum, Forest, Medicinal Plants, Species Diversity, Survey Methods.